Synergistic Antibiofilm Potentials of Essential Oil of Clove (Eugenia Caryophyllata) and Nisin Against Bacillus Cereus Biofilms - Cao, Haixin (International Journal of Public Health and Medical Research, 2026)
Bacillus cereus is an important foodborne pathogen that can contaminate a wide range of foods and form persistent biofilms on food and food-contact surfaces, thereby increasing the risk of spoilage and cross-contamination. In response to growing interest in natural antimicrobial agents for food preservation, this study investigated the antimicrobial and antibiofilm activities of nisin and clove essential oil against B. cereus, with particular emphasis on their potential synergistic effects when used in combination. Antimicrobial activity was evaluated using agar diffusion and broth tube dilution assays, while biofilm formation and inhibition were assessed using Congo red agar and crystal violet microtiter plate assays. The results showed that nisin exhibited strong antimicrobial activity against B. cereus, whereas clove essential oil alone showed little inhibitory effect on bacterial growth under the tested conditions. However, clove essential oil enhanced the antimicrobial activity of nisin when used in combination. In the antibiofilm assay, nisin alone showed strong activity, with all tested concentrations inhibiting biofilm formation by more than 90%. Clove essential oil alone also reduced biofilm formation, with inhibition ranging from 68.5% to higher levels depending on concentration. The combination treatments produced the greatest antibiofilm effects, with the most effective treatment, 250 IU/mL nisin combined with 1500 IU/mL clove essential oil, achieving 98.6% inhibition. Overall, these findings suggest that although clove essential oil alone was ineffective against planktonic growth, it contributed substantially to enhanced antimicrobial and antibiofilm activity when combined with nisin. The combination of nisin and clove essential oil may therefore represent a promising natural strategy for controlling B. cereus and its biofilm in food-related environments.